Literature Study: The Right Method in Learning History to Improvement the Quality of Learning - Sarah, Fidlia Mae; Djono, Djono; Ediyono, Suryo (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
History learning plays an important role for the generation of the Indonesian nation. In this regard, it is necessary to equalise perceptions and innovate regarding the models and strategies used in learning history in schools. This research uses the literature review method that is relevant to the title and topic raised through the internet, articles, books and magazines and thesis. From the results of the study we found that there are at least four models that we found effective in improving the quality of history learning in schools, namely 1) differentiation learning model, 2) inquiry learning model, 3) contextual learning model and 4) PAIKEM learning model. The purpose of this article is to provide new insights for teachers and prospective teachers to improve the quality of history learning in schools so that it is not monotonous and important to instil historical thinking in students.